Perancangan Mesin Pengiris Tempe Ergonomis - Daumi Rahmatika; Novrianti; Hari Purnomo (Jurnal INOVATOR, 2020)
As Small and Medium size enterprise(SME) still using manual and simple tools in their operation as done by Bude Wagino SME which is located at Sungai Bahar,Batanghari. This SME specialized at making kripik Tempe(Tempe chips). Based on observation and interview at the SME, the workers complain that they experience over fatigue, back pain and sore muscle in their arms. The purpose of this research is to design ergonomic slicer tempe tools by using  ENASE concept. This research using mixed method which using antropometri data such as height of sitting elbow,normal range,far reach, and grip width as quantitative method. As qualitative method used for interview the workers. The data of workers percentile will be used as based design of the tools.By using the tool will be expected to decrease the workers complain and can increase the productivity.